2017
DOI: 10.18632/oncotarget.14760
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of abnormally expressed lncRNAs in ovarian carcinoma: a systematic review and meta-analysis

Abstract: Ovarian cancer (OC) is the most deadly gynecological cancer and it is urgently needed to find a new marker for the progress of OC. Many long noncoding RNAs (lncRNAs) have been reported to be aberrantly expressed in ovarian carcinoma, and may serve as prognostic markers. Therefore, we conducted this meta-analysis to gain a better understanding of the prognostic value of lncRNAs in patients with varian carcinoma. We systematically searched PubMed, EMBASE, and Web of Science. A total of 13 eligible studies, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…All of these findings show that HOTAIR was an independent prognostic factor for predicting OS in patients with OC. A recent meta-analysis indicated that lncRNAs, including HOTAIR, could function as potential prognostic markers for patients with OC and that high HOTAIR expression was associated with shorter OS in OC [106]. Mechanistically, the results demonstrated that ectopic HOTAIR expression induced the activation of NF-κB signaling during DNA damage response (DDR) and induced the expression of the key NF-κB target gene interleukin-6 [106]; these actions indicate the critical role of HOTAIR in cellular senescence and platinum sensitivity.…”
Section: Hotair In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…All of these findings show that HOTAIR was an independent prognostic factor for predicting OS in patients with OC. A recent meta-analysis indicated that lncRNAs, including HOTAIR, could function as potential prognostic markers for patients with OC and that high HOTAIR expression was associated with shorter OS in OC [106]. Mechanistically, the results demonstrated that ectopic HOTAIR expression induced the activation of NF-κB signaling during DNA damage response (DDR) and induced the expression of the key NF-κB target gene interleukin-6 [106]; these actions indicate the critical role of HOTAIR in cellular senescence and platinum sensitivity.…”
Section: Hotair In Ovarian Cancermentioning
confidence: 99%
“…A recent meta-analysis indicated that lncRNAs, including HOTAIR, could function as potential prognostic markers for patients with OC and that high HOTAIR expression was associated with shorter OS in OC [106]. Mechanistically, the results demonstrated that ectopic HOTAIR expression induced the activation of NF-κB signaling during DNA damage response (DDR) and induced the expression of the key NF-κB target gene interleukin-6 [106]; these actions indicate the critical role of HOTAIR in cellular senescence and platinum sensitivity. Thus, the NF-κB-HOTAIR regulatory axis triggered a positive-feedback loop cascade during DDR and contributed to cellular senescence as well as chemotherapy resistance in ovarian and other types of cancer [107].…”
Section: Hotair In Ovarian Cancermentioning
confidence: 99%
“…HOTAIR is upregulated in endometrial cancer (EC) (Smolle, et al 2015) and contributes to cisplatin-resistance by inhibiting autophagy (Sun, et al 2017b). HOTAIR is highly expressed in ovarian cancer (Luo, et al 2017), in endometrial, ovarian, and cervical cancers (Li, et al 2017a), and in thyroid cancers ), including PTC (Zhu et al 2016).…”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 99%
“…Interestingly, as DNA is unlikely to change, HOTAIR DNA-based prognostic biomarkers could be used as reliable classifiers to distinguish patients for personalized treatment. Moreover, a recent meta-analysis of data from 13 studies revealed 8 up-regulated and 5 down-regulated lncRNAs associated with poor prognosis, and of these lncRNAs, higher expression of HOTAIR was associated with shorter OS in patients with OC [78].…”
Section: Lncrna Signature As a Diagnostic And Prognostic Biomarker Of Ocmentioning
confidence: 99%